EXTEND THE SHELF LIFE AND IMPROVING SENSORY PROPERTIES OF WHITE SOFT CHEESE BY ADDING CELERY …..LEAVES - & et al., awda (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aime to investigate the effect of addition different concentration of celery leaves to white soft cheese ,Treated cheese between 2018-2019, ,The finely Celery (Apium graveolens) leaves were adding to crude white cheese after texturizing in three leveles included (A,B,C) in addition of control antimicrobial activity of celery treated cheese against total account bacteria and coliform bacteria was estimated during (0, 5, 10, 15, 20) days. The results were shown that the higher concentration of celery in treated cheese, had a lower concentration of protein, lipid and ash content ( 16.81,15.13 and 4.30% respectively, but it had a higher moisture content 59.50%.also the total bacteria counts were decreasing significantly (0.05 P)with accumulative of cheese during astorage periods, it was reached to 1.3x105 , 9.5x103, 9x103, 7.62x103 , 1.05x104 (cfu/g) respectively comparing with control samples,the number of coliform bacterial in celery treated cheese, at concentrations 15% was achieved significant difference comparing with other samples ( 8x103,10.2x104, 9.7x104 , 8.9x105, 9.5x107( log cfu/g ) respectively.